When young people with intellectual disabilities and autism hit puberty : a parents' Q&A guide to health, sexuality and relationships - Brown, Freddy Jackson (Jessica Kingsley Publishers, 2016)
Puberty, personal hygiene, and sex can be difficult topics to broach with your child, especially when they have an intellectual disability or autism. The authors of this guide provide honest answers to challenging questions and provide solutions to the dilemmas that many parents face on a daily basis. Structured around issues related to puberty and emerging sexuality in children with disabilities or autism, such as physical changes, mood swings, and sexual behaviour, the book presents case studies alongside practical guidance on how to overcome problems that commonly arise. The book also explains laws relevant to disability and sexuality and suggests appropriate sex education programmes to meet the needs of differing degrees of disability.